Formation and Accumulation of Acetaldehyde and Strecker Aldehydes during Red Wine Oxidation - Bueno, Mónica; Marrufo-Curtido, Almudena; Carrascón, Vanesa; Fernández-Zurbano, Purificación; Escudero, Ana; Ferreira, Vicente (Frontiers in Chemistry, 2018)
The main aim of the present work is to study the accumulation of acetaldehyde and Strecker aldehydes (isobutyraldehyde, 2-methylbutanal, isovaleraldehyde, methional, phenylacetaldehyde) during the oxidation of red wines, and to relate the patterns of accumulation to the wine chemical composition. For that, eight different wines, extensively chemically characterized, were subjected at 25°C to three different controlled O2 exposure conditions: low (10 mg L-1) and medium or high (the stoichiometrically required amount to oxidize all wine total SO2 plus 18 or 32 mg L-1, respectively). Levels of volatile aldehydes and carbonyls were then determined and processed by different statistical techniques. Results showed that young wines (<2 years-old bottled wines) hardly accumulate any acetaldehyde regardless of the O2 consumed. In contrast, aged wines (>3 years-old bottled wines) accumulated acetaldehyde while their content in SO2 was not null, and the aged wine containing lowest polyphenols accumulated it throughout the whole process. Models suggest that the ability of a wine to accumulate acetaldehyde is positively related to its content in combined SO2, in epigallocatechin and to the mean degree of polymerization, and negatively to its content in Aldehyde Reactive Polyphenols (ARPs) which, attending to our models, are anthocyanins and small tannins. The accumulation of Strecker aldehydes is directly proportional to the wine content in the amino acid precursor, being the proportionality factor much higher for aged wines, except for phenylacetaldehyde, for which the opposite pattern was observed. Models suggest that non-aromatic Strecker aldehydes share with acetaldehyde a strong affinity towards ARPs and that the specific pattern of phenylacetaldehyde is likely due to a much reduced reactivity towards ARPs, to the possibility that diacetyl induces Strecker degradation of phenyl alanine and to the potential higher reactivity of this amino acid to some quinones derived from catechin. All this makes that this aldehyde accumulates with intensity, particularly in young wines, shortly after wine SO2 is depleted.